Joint Effusions And Purpura In Multiply-Transfused Adult Beta-Thalassemia- Clinical Pointers To Diagnosis Of Scurvy - Prakash, A; Pandey, AK (Kathmandu University Medical Journal, 2015)
Periodic transfusions and effective chelation have ensured that thalassemics survive in to adulthood but their life is punctuated by peculiar problems in adulthood. Three cases of scurvy are being reported presenting uniquely as purpura, right hip joint effusion and right knee joint effusion with haemorrhage in prepatellar and retropatellar bursae, respectively over an 18 month period (2009-2010). The first two cases did give a history of gum bleed. None had any coagulation disturbance or transfusion-transmitted infections or connective tissue disorder. All the three cases responded dramatically to vitamin C supplementation. It is imperative to keep in mind that recurrent blood transfusions are associated with a state of sub-clinical vitamin C deficiency and overt scurvy may manifest as cumulative number of transfusions increase, as in adult thalassemics.Kathmandu Univ Med J 2013; 11(4): 360-362